Hubungan Karakteristik Tenaga Pemorsi dengan Ketepatan Porsi dan Energi pada Standar Diet Diabetes Melitus di RSUD Embung Fatimah - Nurul Oktavia Asyriani; Siska Pratiwi; Nelli Roza (Lembaga Pengembangan Kinerja Dosen, 2025)
Hospitals play a vital role in providing standardized meals for managing diabetes mellitus (DM). However, inaccuracies in portion sizes and energy content remain prevalent. To analyze the relationship between portioning personnel characteristics and portion accuracy and energy content in DM diet standards at RSUD Embung Fatimah. This cross-sectional study involved eight portioning personnel. Primary data were collected through portion observation and energy analysis, while secondary data came from documents and interviews. Data were analyzed using Spearman Rank correlatio. No significant relationship was found between personnel characteristics and portioning accuracy or energy content (p>0.05). Work experience and educational level do not influence portioning accuracy. Training and standardized tools are recommended to improve portioning practices.